Comparative study of the accuracy of CBCT implant site measurements using different software programs - Asma'a A. Al-Ekrish (Elsevier, 2021)
Purpose: To measure and compare the accuracy of the linear dimensions of implant sites recorded from cone beam computed tomography (CBCT) images using Blue Sky Plan, coDiagnostiX, and RadiAnt. Materials and Methods: Five human dry skulls were imaged with a CBCT device then sectioned to obtain sample transverse cross-sections of the edentulous ridges, and the height and width of the ridge were measured with a digital caliper to provide the gold standard measurements. The CBCT datasets were exported in DICOM format and imported into the three test software programs which were used to obtain reformatted sectional images corresponding to the sample transverse cross-sections, and the height and width of the edentulous ridge was recorded using the linear measurement tool. Reliability of the measurements were measured using the intraclass correlation coefficient. One-sample t-test (test value: zero) was used to test the statistical significance of the mean of the absolute errors for each software program. Analysis of Variance with Repeated Measures was used to test the statistical significance of the difference between the means of the absolute errors obtained by the different software programs. Statistical significance was set at a p-value of 0.05. Results: The reliability of the gold standard and image measurements were excellent. All three software programs demonstrated a statistically significant mean absolute measurement error of between 0.43 and 0.56 mm (p-value < 0.01), but no significant difference in error values was found between any of the tested programs (p- value = 0.18). Conclusions: There was no statistically significant difference in accuracy of linear CBCT measurements of implant sites recorded using Blue Sky Plan, coDiagnostiX, and RadiAnt.